EVALUASI DAMPAK PEMEKARAN DAERAH TERHADAP KINERJA EKONOMI DAN KINERJA PELAYANAN PUBLIK DI KOTA SERANG - Furry P.R, Ratri; Sasana, Hadi (Diponegoro Journal of Economics, 2013)
Administrative region formation is a process of administrative region division which is conducted in order to improve the welfare of the occupants of the respective region through the acceleration of economic development and the improvement of capacity in public services. The city of Serang, formed out of the municipality of Serang, Banten regency, was established with such goals in mind. This research is conducted both to measure the economic performance and public services performance of the city of Serang after administrative formation (2009-2011) and to compare the results with similar data from its municipality of origin.This research uses indexing method. The indexing method is used to compare the performance between the newly established administrative region and its municipality of origin.Index calculation results that the performance of economic and public services of the city of Serang shows that the city is comparable to municipality of Serang with slightly better results.